Compressibility of binary mixtures of associating liquids - WACIŃSKI, Marek; BEBEK, Krzysztof; ZORĘBSKI, Edward (Archives of Acoustics, 1984)
This paper presents the application of ultrasonic methods to investigate the structure of liquid mixtures of polyhydroxyalcohols (glycerol-butanediol-1.3 and glycerol-2-methylpentanediol-2.4).Measurements were carried out on the propagation of ultrasonic waves at a frequency f = 2.5 MHz over the temperature range 283-303 K and on density over the temperature range 273-303 K for the alcohols and mixtures.Excess compressibilities were calculated for the systems of interest. It was shown that the compressibility of mixtures of associating liquids was determined not only by specific intermolecular interactions, but also a major role is played by steric factors (the degree of filling the space).